2022
DOI: 10.1111/pai.13887
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab in daily practice for the treatment of pediatric atopic dermatitis: 28‐week clinical and biomarker results from the BioDay registry

Abstract: Background: Dupilumab has proven to be an effective and safe treatment for atopic dermatitis (AD) in pediatric patients in clinical trials. However, few daily practice studies are available. The aim of this study is to evaluate the effect of 28 weeks dupilumab treatment on effectiveness, safety, and serum biomarkers in pediatric patients with moderate-to-severe AD in daily practice. Methods: Patients visited the outpatient clinic at baseline, 4, 16, and 28 weeks of treatment. Disease severity was assessed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…EASI‐75 was achieved by 75% of patients in both Napolitano's and our studies, but our patients more often achieved EASI‐90 (71% in our study vs. 9% in theirs) 9 . Another multicenter cohort study reported EASI‐75 being achieved by 43% and EASI‐90 being achieved by 16% of patients at week 16 11 …”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…EASI‐75 was achieved by 75% of patients in both Napolitano's and our studies, but our patients more often achieved EASI‐90 (71% in our study vs. 9% in theirs) 9 . Another multicenter cohort study reported EASI‐75 being achieved by 43% and EASI‐90 being achieved by 16% of patients at week 16 11 …”
Section: Discussioncontrasting
confidence: 54%
“…Compared to other case series, 7–11 our patients had experienced more difficult‐to‐treat AD based on the number of previous systemic therapies (Tables 1 and 2); however, similar EASI improvements were achieved. In another case series, patients received systemic corticosteroids (44%), cyclosporine (25%), and methotrexate (7%) 9 while, in our cohort, more patients received methotrexate (45%) and fewer patients received systemic corticosteroids (35%) and cyclosporine (18%).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The role of the pruritogen periostin in peripheral neural sensitization has been recently reported. Increased periostin levels have been found in chronic itchy skin conditions such as AD, PN, and bullous pemphigoid, and positively correlated with itch severity ( Ariëns et al, 2020 ; Hashimoto et al, 2021 ; Kamphuis et al, 2022 ; Sans-de San Nicolàs et al, 2023 ). Periostin is an intracellular matrix protein thought to be produced by epidermal keratinocytes and dermal fibroblasts, and binds to its receptor integrin α V β3, causing immune cells to release itch cytokines IL-4, IL-13, IL-31 and inducing sensory nerve fiber sensitization by direct activation of integrin alpha B receptor ( Masuoka et al, 2012 ; Hashimoto and Yosipovitch, 2019 ; Izuhara et al, 2019 ; Mishra et al, 2020 ).…”
Section: Peripheral Neural Sensitization In Chronic Itchmentioning
confidence: 99%
“…Although a highly effective and safe drug, dupilumab is associated with conjunctivitis. 2 In AD clinical trials, rates of conjunctivitis vary, which may be due to the different MedDRA codes that can capture conjunctivitis-related events. We analyzed recent AD clinical trials to illustrate how an understanding of MedDRA may be helpful when interpreting the rate of conjunctivitis observed with dupilumab treatment and the safety of drugs more generally.…”
mentioning
confidence: 99%